SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI HARAPAN BARU - Rudi Hartanto; Mahmud Yusuf; Niken Retnowati (LPPM Universitas Widya Dharma, 2021)
The data processing that took place at the Harapan Baru Savings and Loans Cooperative was not computerized or still manual such as processing customer data, savings data, loan data and installment data. Officers are still using handwriting and are backed up on paper. With the increase in customers, the Harapan Baru Cooperative, especially cooperative officers, will experience difficulties so that the service is less than optimal. This results in data processing taking a long time and if something happens it is possible that there will be no data backup because it was written manually. The security of managed data is also vulnerable to the risk of being lost, so it must be maintained. The purpose of this research is to build an information system in the Harapan Baru Savings and Loans Cooperative. The research method used for data collection by observation and direct interviews with the leadership of the Harapan Baru Cooperative to obtain the necessary information. Materials and research materials in the form of information about the Harapan Baru Cooperative. The tools used in this research were a laptop unit and Microsoft Visual Foxpro 9.0 software. The results of the study obtained a desktop-based system in the form of a savings and loan information system application at the Harapan Baru Cooperative. Applications can be used as an alternative for cooperatives to facilitate customer data management by presenting information quickly, accurately and able to save time so that the required reports will be easily obtained and on time.